2004
DOI: 10.1023/b:anto.0000024913.94410.05
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Bacillus thuringiensis strains from Argentina

Abstract: Bacillus thuringiensis INTA 7-3, INTA 51-3, INTA Mo9-5 and INTA Mo14-4 strains were obtained from Argentina and characterized by determination of serotype, toxicity, plasmid composition, insecticidal gene content ( cry and vip ) and the cloning of the single- vip3A gene of the INTA Mo9-5 strain. The serotype analysis identified the serovars tohokuensis and darmstadiensis for the INTA 51-3 and INTA Mo14-4 strains, respectively, whereas the INTA Mo9-5 strain was classified as "autoagglutinated". In contrast to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Genes coding for Vip3 proteins are commonly found among B. thuringiensis strains, and hence, some studies have even found them in 50% and up to 87% of the strains tested and in Ͼ90% of strains carrying cry1 and cry2 genes (20,21,(40)(41)(42)(43)(44). vip3 genes are ϳ2.4 kb in length, and they are normally carried on large plasmids (43,45), although in some cases, they have been proposed to be located in the bacterial chromosome (46). Many strategies for screening of B. thuringiensis isolates have been performed with the aim of isolating new vip3 genes (19,20,25,42,(46)(47)(48)(49)(50)(51)(52).…”
Section: The Vip3 Lepidopteran-active Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes coding for Vip3 proteins are commonly found among B. thuringiensis strains, and hence, some studies have even found them in 50% and up to 87% of the strains tested and in Ͼ90% of strains carrying cry1 and cry2 genes (20,21,(40)(41)(42)(43)(44). vip3 genes are ϳ2.4 kb in length, and they are normally carried on large plasmids (43,45), although in some cases, they have been proposed to be located in the bacterial chromosome (46). Many strategies for screening of B. thuringiensis isolates have been performed with the aim of isolating new vip3 genes (19,20,25,42,(46)(47)(48)(49)(50)(51)(52).…”
Section: The Vip3 Lepidopteran-active Proteinmentioning
confidence: 99%
“…vip3 genes are ϳ2.4 kb in length, and they are normally carried on large plasmids (43,45), although in some cases, they have been proposed to be located in the bacterial chromosome (46). Many strategies for screening of B. thuringiensis isolates have been performed with the aim of isolating new vip3 genes (19,20,25,42,(46)(47)(48)(49)(50)(51)(52). At the time of writing of this review, there have been 54 vip3Aa, 2 vip3Ab, 1 vip3Ac, 4 vip3Ad, 1 vip3Ae, 3 vip3Af, 15 vip3Ag, 1 vip3Ah, 1 vip3Ai, 2 vip3Ba, 3 vip3Bb, and 4 vip3Ca genes reported (9).…”
Section: The Vip3 Lepidopteran-active Proteinmentioning
confidence: 99%
“…Conversely, evidence indicating that the gene is chromosomally located has been presented (16), although that conclusion was based on the examination of a single isolate. The widely divergent values recorded for carriage of this gene among strains of B. thuringiensis may indicate that the acquisition of this gene, possibly via horizontal gene transfer from other soil microbes, was a relatively recent event in the evolution of B. thuringiensis.…”
Section: Resultsmentioning
confidence: 99%
“…In the long term, our goal is to find new insecticidal proteins from the local B. thuringiensis insecticidal gene pool to serve as a supply for the development of new tools for crop protection. The entries of the collection have been characterized to different extents [e.g., Benintende et al, 2000;Franco-Rivera et al, 2004;Sauka et al, 2010a].…”
Section: Introductionmentioning
confidence: 99%